Mechanical performance of building modules during road transportation. (15th November 2020) - Innella, Filomena; Bai, Yu; Zhu, Zhihui
Highlights: Numerical framework to assess performance of building modules in transportation. Experimental results to clarify fatigue performance of non-structural elements. Random vibration analyses of stress responses for modules during transportation. Damage level evaluation of non-structural elements due to transportation vibration. Abstract: Modular construction uses prefabricated structures as building modules, transported from the factory to the construction site, for the final assembly. Despite the ongoing interest in modular construction, specific design practices have not been fully developed, particularly with consideration of non-traditional loadings, such as those during transportation and lifting. The transportation stage, in particular, deserves further investigation as building modules often exhibit damages typically in non-structural elements such as plasterboard panels and their connections. In this context, this paper aims to develop a framework to assess the performance of building modules and evaluate the damage levels of non-structural elements in transportation. This framework includes the development of a finite element (FE) modelling of a building module to perform random vibration analyses in the frequency domain, the assessment of the fatigue performance of non-structural elements experimentally, and the implementation of spectral numerical approaches to evaluate the damage levels. The damage levels of non-structural elements thus obtained are discussed according to different features of the accelerations in transportation, i.e., stress probability, accelerometer position, speed range, and road roughness.